(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
External fixation is a common technique for the treatment and stabilization of bone fractures using pins or wires. Different designs were considered, but all of them present limitations such as high weight (they are based on heavy frame), not comfortable to use and not customized to individual patients. Therefore, this paper proposes a novel lightweight customized external fixator, overcoming some of the identified limitations. It also investigates the mechanical characteristics of the newly developed fixator considering different stages of healing using finite element method.